2015
DOI: 10.1039/c5dt00056d
|View full text |Cite
|
Sign up to set email alerts
|

Counter anion dependent gradual spin transition in a 1D cobalt(ii) coordination polymer

Abstract: One Co(ii) SCO coordination polymer [Co(enbzpy)(μ1,5-dca)]n(PF6)n (·PF6) has been isolated and characterised structurally and magnetostructurally. The properties of ·PF6 are compared with the reported perchlorate analogue [Co(enbzpy)(μ1,5-dca)]n(ClO4)n (·ClO4). The gradual spin transition in ·PF6 in contrast to an abrupt spin transition with a hysteresis loop in ·ClO4 has been analysed in terms of structural factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The ICP-OES analysis indicated that the {M(hfac)2} CP site is 70% Co and 30% Zn. The structural refinement of this site, as a mixture of Co & Zn, gave values consistent with this analysis (the zinc occupancy at 100 K was 0.34(5), at 150 K: 0.15 (6) and at 200 K: 0.39(6), averaging to 30% Zn occupancy). Since the same crystal was used throughout the variable temperature structural analysis, the occupancy of the site was fixed as 30%…”
Section: X-ray Crystallographysupporting
confidence: 78%
See 1 more Smart Citation
“…The ICP-OES analysis indicated that the {M(hfac)2} CP site is 70% Co and 30% Zn. The structural refinement of this site, as a mixture of Co & Zn, gave values consistent with this analysis (the zinc occupancy at 100 K was 0.34(5), at 150 K: 0.15 (6) and at 200 K: 0.39(6), averaging to 30% Zn occupancy). Since the same crystal was used throughout the variable temperature structural analysis, the occupancy of the site was fixed as 30%…”
Section: X-ray Crystallographysupporting
confidence: 78%
“…In some cases, a structural phase transition accompanies the SCO. To date, SCO has been reported for only a handful of cobalt CPs [4][5][6][7][8]. One of these families of SCO CPs has the general formula [CoX2(pyterpy)] where X = Cl -, Bror NCSand pyterpy = 4'-(4-pyridyl)-2,2':6',2''-terpyridine [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the perchlorate counterion undergoes reorientation that affects the anion- interactions with the dicyanamide bridge, which seem to play a significant role in the cooperative character of the SCO transition. The phenomenon was later confirmed by studies of a hexafluorophosphate salt of the same complex, which undergoes a gradual and nonhysteretic SCO transition [57]. The non-coordinating bulky hexafluorophosphate counterion does not take part in the intermolecular interactions around the cobalt center, the result being a much less well-defined SCO conversion.…”
Section: Spin Crossover In One Dimensional Cobalt Coordination Polymersmentioning
confidence: 87%
“…However, a ligand based on terpyridine and its derivatives have been used intensively. , It is reported that the coordination environment around a cobalt­(II) center having a CoN 6 surrounding with all six donating nitrogen atoms coming from two neutral tridentate ligands generates [Co­(L-N 3 ) 2 ] 2+ SCO complexes. In addition, extremely rare reports have explored the SCO properties of cobalt­(II) with ligand systems different from terpyridine. …”
Section: Introductionmentioning
confidence: 99%